Using Storytelling to Enhance Critical Listening (2024)
ABSTRACT: This action research project explores the integration of storytelling strategies to encourage critical listening among third-grade students in a public institution in the municipality of Copacabana, Antioquia. Data collection methods included student-teacher journals, initial diagnostic tests, self-assessment, interviews with the cooperating teacher, students' classwork, voice recordings, and observations from an external observer. The research was structured into two cycles that incorporated various storytelling techniques such as vivid storytelling, multisensory interaction, and visual elements. In each session pre-listening, while-listening, and post-listening activities were included and designed to activate prior knowledge, provide context for the listening task, and use questions as a main strategy for encouraging critical thinking and story comprehension. In the final phase of the research, the collected data was analyzed to evaluate the effectiveness of the storytelling techniques. The results demonstrated that the use of storytelling is an effective pedagogical tool for developing critical listening skills in young learners.